(untitled) (Ciudades, 2018)
The present work studies Venezuela’s estates as a key element of the country’s heritage. The estates are examined on several of their historical dimentions: as an articulative element of territory, as an unit of economic and social development, and as a theme for architectonic composition. Special emphasis is given to the answers that the estates have given to geographical, economic and social conditions of the historic formation of the Central Region. In that sense, it stresses the important process of sinthesis that was obained on those microcosms, on which there was room for edifications, society and landscape. The work presents as well some of the problems related to the preservation of this heritage elements, in virtue of the gradual dissapearance of the economic structure and the social order in which they were born.